1995
DOI: 10.1242/jcs.108.6.2525
|View full text |Cite
|
Sign up to set email alerts
|

Sperm exocytosis reconstructed in a cell-free system: Evidence for the involvement of phospholipase c and actin filaments in membrane fusion

Abstract: We used a cell-free system to study membrane fusion during sperm exocytosis (acrosome reaction). Extracted bovine sperm plasma and outer acrosomal membranes were labeled with chlorophyll a or DCY, respectively. The occurrence of membrane fusion is indicated by the ability of the probes to diffuse from one membrane species to another which is revealed by resonance energy transfer between the two probes. We have previously shown using this system that the requirement of capacitation for sperm exocytosis is retai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…This was the first report of a model system in which fusion was induced by a catalytic agent. Other authors have pointed out the putative role of phospholipase C in physiological cell fusion events (Roldan & Harris, 1989;Liu et al, 1993;Spungin et al,1995). While the degree of implication of phospholipase C in cell membrane fusion remains to be established, the enzyme-driven liposome fusion process shows nevertheless remarkable regulatory properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the first report of a model system in which fusion was induced by a catalytic agent. Other authors have pointed out the putative role of phospholipase C in physiological cell fusion events (Roldan & Harris, 1989;Liu et al, 1993;Spungin et al,1995). While the degree of implication of phospholipase C in cell membrane fusion remains to be established, the enzyme-driven liposome fusion process shows nevertheless remarkable regulatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipases C have been comparatively less studied, in spite of their essential role in several aspects of metabolic regulation (Berridge et al, 1987;Exton, 1990;Haines et al, 1992). Phospholipases C may equally be involved in membrane fusion events (Roldan & Harris, 1989;Liu et al, 1993;Spungin et al, 1995). Previous investigations from this laboratory have revealed that the catalytic activity of phospholipase C may promote phospholipid vesicle fusion (Nieva et al, 1989(Nieva et al, , 1993(Nieva et al, , 1995.…”
mentioning
confidence: 99%
“…The inescapable question on the biological relevance of the above observations cannot receive a fully satisfactory answer as yet. However, phospholipase C (and Ca 2+ in millimolar concentrations) has been found to be involved in a physiological fusion process, namely, sperm exocytosis, and is probably important in other exocytotic processes (Rolda ´n & Harrison, 1989;Spungin et al, 1995). Moreover, the growing consensus on a single topological mechanism underlying the various fusion processes (see introduction) increases the validity and relevance of studies involving model systems.…”
Section: Discussionmentioning
confidence: 99%